The Role of Information Systems Auditors in Enhancing Compliance with SOX and FFIEC Standards in Banking (gjstudies, 2016)
This research examines the critical role of Information Systems auditors inenhancing compliance with Sarbanes-Oxley Act (SOX) Section 404 and FederalFinancial Institutions Examination Council (FFIEC) guidelines within the banking sector. Through comprehensive analysis of 320 compliance audits across 65U.S. banking institutions from 2012-2015, this study develops a multidimensionalframework for evaluating IT control effectiveness under regulatory standards. Thefindings demonstrate that organizations with integrated IS audit functions achieve42% higher compliance rates with SOX Section 404 requirements and 58% fasterremediation of FFIEC-identified control deficiencies. The research introduces theRegulatory Compliance Maturity Model (RCMM), which identifies five critical dimensions influencing audit effectiveness: control environment assessment, documentation rigor, testing methodology, deficiency management, and continuous monitoring. Statistical analysis reveals strong correlation (r=0.81, p¡0.001) between RCMMscores and regulatory examination outcomes. Banks with mature IS audit capabilities experienced 67% fewer material weaknesses in internal controls and reducedcompliance-related costs by 31% through optimized audit processes. These findings underscore the strategic value of IS auditors in navigating complex regulatorylandscapes and provide practical frameworks for enhancing compliance effectivenesswhile reducing associated burdens.